1999
DOI: 10.1111/j.1469-7793.1999.0223o.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of nitric oxide within the coeliac plexus is involved in the organization of a gastroduodenal inhibitory reflex in the rabbit

Abstract: The autonomic nervous system is involved in the regulation of visceral function, including the regulation of digestive tract motility. One characteristic of this system is that the nervous regulatory structures are not localized exclusively in the cerebrospinal axis. From a classic point of view, it could be described as having an intrinsic level of regulation located in the viscera and an extrinsic level of regulation in the prevertebral ganglia and central nervous structures, with each level of regulation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…This explains why the conduction of excitation remains limited to the specific network activated by gastric distension. In a previous work we have shown that superfusion of the coeliac plexus with carboxyPTIO inhibited the GIR [2]. This indicated that NO is the neurotransmitter released in the extracellular space by the gastric afferent fibres to activate the ganglionic neurons.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…This explains why the conduction of excitation remains limited to the specific network activated by gastric distension. In a previous work we have shown that superfusion of the coeliac plexus with carboxyPTIO inhibited the GIR [2]. This indicated that NO is the neurotransmitter released in the extracellular space by the gastric afferent fibres to activate the ganglionic neurons.…”
Section: Resultsmentioning
confidence: 85%
“…When the nerve trunks were selectively superfused with 2 µM 1H-[1], [2], [4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ, a selective inhibitor of the NO-activated soluble guanylate cyclase) for at least 30 min, the gastric distension failed to affect the duodenal contractions significantly (paired t test, non significant, df = 3, Fig. 4f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More precise data concern only fibers secreting nitric oxide (NO). Experiments in rabbits revealed a strong involvement of NO, released in the region of CSMG complex, in the gastro-duodenal inhibitory reflex (Quinson et al, 1999(Quinson et al, , 2000. It was also hypothesized that NO triggers activation of the cyclic guanosine monophosphate (cGMP) pathway in the target cells (Anderson et al, 1994;Quinson et al, 2000).…”
Section: Nerve Fibers Adjacent To Fb-positive Perikaryamentioning
confidence: 97%
“…Notre étude a été effectuée sur une préparation in vitro composée d'un centre nerveux périphérique, le plexus coeliaque [2], connecté à l'estomac et au duodénum (Figure 1). Nous avons ensuite établi que le neuromédiateur libéré dans le plexus coeliaque lors de ce fonctionnement neuronal non conventionnel est un gaz, le monoxyde d'azote (NO) [3]. À ce stade de nos recherches le mécanisme de Cependant ces radeaux n'avaient encore jamais été mis en évidence dans les élé-ments périphériques du système nerveux végétatif.…”
Section: Un Modèle De Conduction Nerveuse D'excitation Sans Potentielunclassified